Progressive education, modern schools and Egyptian teachers: 1922-1956 - Makar, F (2023)
This dissertation sets out to understand how and why progressive education was adopted in Egypt between 1922 and 1956 by focusing on the lives, experiences and contributions of Egyptian pre-University public schoolteachers. It traces practicing teachers and more senior pedagogues from their initial training, to the first encounter with real-life classrooms, to their active engagement within syndicates and associations, in an attempt to historicise the formation of a professional identity. Progressive education is the thread that weaves these different professional and life episodes together, it therefore occupies a central and pivotal role in the project precisely because it was a pedagogical movement that many teachers believed in. Since the project tells the story of the emergence of a professional identity, it is divided into three parts that follow teachers at their institutions: Tadrib (training), Tadris (teaching), and Tanzim (organizing and advocacy).